Negotiating Metropolitan Spaces and Identities: A Historian's Reading of Tactics in 1920's New York Homicide Trials - D'Cruze, Shani (Social justice, 2005)
Part of a special issue on emerging imaginaries of regulation, control, and repression. The writer discusses New York homicide trials in the early 1920s in terms of their function as moments when the law made violence visible and the conditions of that visibility were that violence became understandable as a product of everyday sociality in working-class neighborhoods. She states that the courtroom asked people to explain their metropolitan living strategies and that witnesses had to translate everyday relationships, circumstances, and violent events into a narrative format acceptable in a antagonistic judicial forum whose culture and often whose language was not their own. She points out that some failed miserably but that others who could take up legible and acceptable subject stances had greater narrative success.